FONTES DE ADUBAÇÃO NITROGENADA NA EXPRESSÃO DO AFILHAMENTO E MASSA DE GRÃOS EM TRIGO - Battisti, Gabriel K.; Bandeira, Taiane; Boff, Jose T.; Wentz, Renan; Diego, Cleverson; Dambros, Diego; Bach, Sandro; Vicenzi, Sandra; Kruguer, Cleusa B.; Silva, Jose A. G. d. (Salão do Conhecimento, 2013)
Resumo